The identification of viral ribonucleotide reductase encoded by ORF23 and ORF141 genes and effect on CyHV-2 replication - Cheng, Wenjie; Chen, Qikang; Ren, Yilin; Zhang, Ye; Lu, Liqun; Gui, Lang; Xu, Dan (Frontiers in Microbiology, 2023)
dNTPs are important for the replication of herpesviruses which have evolved a Ribonucleotide reductase strategy to cope with the lack of dNTPs in cells. Although Ribonucleotide reductase is not required for herpesviruses DNA synthesis and replication, its activity was important for viral replication. Phylogenetic tree and protein conserved domain analysis indicated that CyHV-2 proteins, ORF23 and ORF141, had high homology with Ribonucleotide reductase. In addition, this study also demonstrated that the expression of ORF23 and ORF141 increased at both the transcriptional and translational levels as CyHV-2 replicated in GICF cells, and both ORF23 and ORF141 proteins showed Ribonucleotide reductase activities. Cell co-localization experiments identified that CyHV-2 proteins ORF23 and ORF141 were located around the nucleus. The interaction between ORF23 and ORF141 was directly proved using the Co-immunoprecipitation technology and recombinant proteins of CyHV-2 ORF23 and ORF141 expressed in prokaryotes showed activities of Ribonucleotide reductase when they bound to each other in vitro. SiRNA-mediated silencing of viral genes Orf23 and Orf141 inhibited the replication of CyHV-2. Hydroxyurea, a Ribonucleotide reductase inhibitor, was found to suppress the replication of CyHV-2 in GiCF cells and inhibit the activity of CyHV-2 Ribonucleotide reductase in vitro. All these results indicated that CyHV-2 proteins ORF23 and ORF141 function as Ribonucleotide reductase whose activity are important for CyHV-2 replication.